A field scale facility to evaluate the effect of soil organic matter content of sod‐established St. Augustinegrass lawns on nitrate‐nitrogen leaching. Issue 1 (12th January 2021) - Park, Dara M.; Cisar, John L.; Snyder, George H.; Fidanza, Michael A.; Williams, Karen E.
Abstract: A field scale facility was constructed to investigate the impact of a wide range of potential management parameters on nitrate (NO3 ‐N) leaching from St. Augustinegrass [ Stenotaphrum secundatum (Walt.) Kuntze] turf. The facility was built to identify and quantify background NO3 ‐N sources and concentrations before turf cultural management factors were applied, and to examine how establishment of sod with two contrasting soil organic matter (SOM) contents influence NO3 ‐N concentrations in percolate and leachate. The performance of the facility's irrigation and vadose zone percolate sampling units were evaluated and found acceptable. St. Augustinegrass sod with a 2.5 cm rootzone containing either 4% or 10% SOM was installed and maintained at this facility. The NO3 ‐N amounts in percolate and leachate were nearly proportional to the amount of SOM associated with the sod rootzones at 4% and 10%, respectively. Based on this investigation, SOM content in the rootzone attached to sod and within the soil which sod is placed influences NO3 ‐N concentration in the rootzone and leachate. Therefore, SOM should be considered in best management practices for lawncare. This facility will allow for future investigations on cultural management strategies aimed at decreasing the potential for NO3 ‐N leaching from St. Augustinegrass lawns.